2017
DOI: 10.1097/01.nep.0000000000000240
|View full text |Cite
|
Sign up to set email alerts
|

Essential Professional Behaviors of Nursing Students and New Nurses: Hospital Nurse Leader Perspectives Survey

Abstract: The results provide practical information to inform curricula and prepare leaders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Our results firstly showed that the inclusive leadership of Chinese head nurses was not so good. We considered the possible reasons that hospital management system was imperfect and most leaders of head nurses needed to pay much attention to the way of improving their work efficiency, rather than focusing on the leadership (Sortedahl, Persinger, Sobtzak, Farrell, & Jaeger, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Our results firstly showed that the inclusive leadership of Chinese head nurses was not so good. We considered the possible reasons that hospital management system was imperfect and most leaders of head nurses needed to pay much attention to the way of improving their work efficiency, rather than focusing on the leadership (Sortedahl, Persinger, Sobtzak, Farrell, & Jaeger, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In China, head nurses are primary administrators responsible for managing the clinical nursing as well as matters related to patient care and hospital operations while coordinating among doctors, patients, and nurses. These nursing leaders may occasionally tend to be more focused on improving their work efficiency, instead of inclusive leadership behaviour (Sortedahl et al., 2017). This can be remedied through introduction of training and rewards programs which can help draw the focus back to inclusive practices.…”
Section: Discussionmentioning
confidence: 99%
“…That is, in order to have competence in this dimension, the students need to develop components such as communication/interpersonal skills, participation in group work, work commitment, clinical management and initiatives in clinical fields. Sortedahl et al () also highlighted the communication skills, self‐awareness, leadership and ability to manage conflicts and possible changes as the necessary professional behaviours for the students, and emphasized the necessity of obtaining these skills. Since a significant part of nurses’ professional behaviour is formed during their academic education and providing patient care in clinical fields, it is important for the authorities of nursing education to create a suitable platform for the students’ competency in this dimension (Arrigoni et al ; Heshmati Nabavi et al ).…”
Section: Discussionmentioning
confidence: 99%